Combined kinetic and Bean–Rodbell approach for describing field-induced transitions in LaFe11.6Si1.4 alloys. (22nd January 2021) - Moreno-Ramírez, L M; Blázquez, J S; Radulov, I A; Skokov, K P; Gutfleisch, O; Franco, V; Conde, A
Abstract: We propose a combination of the Kolmogorov–Johnson–Mehl–Avrami nucleation and growth theory and the Bean–Rodbell model to describe the field-induced transition in LaFe11.6 Si1.4 alloys. The approach is applied to a set of bulk samples undergoing first-order transitions produced by different routes and including doping effects. The kinetic analysis of both magnetization and demagnetization processes reveals a nucleation and three-dimensional interface-controlled growth for these alloys. Introducing the kinetic process between the metastable and stable solutions of the Bean–Rodbell model, the field dependence of the magnetization/demagnetization processes, including magnetic hysteresis for different magnetic field sweeping rates, is better reproduced than with the pure model.